Neopeltolide and its synthetic derivatives: a promising new class of anticancer agents - Pena-Corona, Sheila I.; Hernandez-Parra, Hector; Bernal-Chavez, Sergio A.; Mendoza-Munoz, Nestor; Romero-Montero, Alejandra; Del Prado-Audelo, Maria Luisa; Leyva-Gomez, Gerardo (Frontiers Media Sa, 2023)
Being the first or second cause of death worldwide, cancer represents the most significant clinical, social, and financial burden of any human illness. Despite recent progresses in cancer diagnosis and management, traditional cancer chemotherapies have shown several adverse side effects and loss of potency due to increased resistance. As a result, one of the current approaches is on with the search of bioactive anticancer compounds from natural sources. Neopeltolide is a marine-derived macrolide isolated from deep-water sponges collected off Jamaica's north coast. Its mechanism of action is still under research but represents a potentially promising novel drug for cancer therapy. In this review, we first illustrate the general structural characterization of neopeltolide, the semi-synthetic derivatives, and current medical applications. In addition, we reviewed its anticancer properties, primarily based on in vitro studies, and the possible clinical trials. Finally, we summarize the recent progress in the mechanism of antitumor action of neopeltolide. According to the information presented, we identified two principal challenges in the research, i) the effective dose which acts neopeltolide as an anticancer compound, and ii) to unequivocally establish the mechanism of action by which the compound exerts its antiproliferative effect.
Keywords: neopeltolide; marine-derived macrolide; cytotoxic; natural antiproliferative drugs; cancer